Thin-layer drying characteristics and modelling of mint leaves undergoing microwave treatment - Ozbek, Belma; Dadali, Gokce (ELSEVIER SCI LTD, 2007)
The effect of microwave drying technique on moisture content, moisture ratio, drying rate, drying time and effective moisture diffusivity of mint leaves (Mentha spicata L.) were investigated. By increasing the microwave output powers (180-900 W) and the sample amounts (25-100 g), the drying time decreased from 12.50 to 3.0 min and increased from 6.60 to 16 min, respectively. To determine the kinetic parameters, the drying data were fitted to various models based on the ratios of the differences between the initial and final moisture contents and equilibrium moisture content versus drying time. Among of the models proposed, the semi-empirical Midilli et al. model gave a better fit for all drying conditions applied. By increasing the microwave output powers and decreasing the sample amounts, the effective moisture diffusivity values ranged from 3.982 x 10(-11) to 2.073 x 10(-10) m(2) s(-1) and from 9.253 x 10(-11) to 3.162 x 10(-11) m(2) s(-1), respectively. The activation energy was calculated using an exponential expression based on Arrhenius equation. The relationship between the drying rate constant and effective moisture diffusivity was also estimated; and gave a linear relationship. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: microwave drying; mint leaves; drying kinetic; activation energy; effective moisture diffusivity; HOT AIR; DESORPTION ISOTHERMS; CARROT; PARAMETERS; QUALITY; Engineering; Food Science & Technology